The Strategies of Translation of Bahasa Indonesia-English in Two Indonesia Tourism Websites - Eldi Valerian (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This study discusses the use of translation strategies in translating Indonesian culture-bound words in two Indonesia tourism website articles. By using a descriptive qualitative analysis method, the translation strategies found in the Indonesian culture-bound words were observed using the theory from Mona Baker (2018). The rank of the most dominant strategies, from the most frequent to the least, used by both translator teams of Wonderful Indonesia and Enjoy Jakarta are loan word with an explanation, word-for-word, cultural substitution, and general word. In the Indonesia culture-bound translation, the most strategy used the culture-bound words is loan word strategy. It is better because instead of translating the Indonesia culture-bound word, the writer keep the culture-bound word in the english version and explain the meaning of the culture-bound word from explaining the history or the ingredients behind the culture-bound words so the international tourists can know the meaning behind the Indonesia culture-bound words without changing the names. In conclusion, both translator teams mostly used loan word strategy as their main strategy in the English translation, but still used other strategy in certain Indonesia culture-bound words. Keywords: translation, translation strategies, culture-bound words